Mass multiplication of AM inoculum: effect of hosts and substrates in rapid culturing of Acaulospora laevis - Kaushish, Sunita; Kumar, Aditya; Mangla, Chhavi; Aggarwal, Ashok (Indian Phytopathology, 2011)
The efficiency of three plant species i.e. lemon grass, onion ( Allium cepa), Sesbania aculeata and the four substrates i.e. sand, farmyard manure, organic manure and vermicompost were evaluated for maximization of Acaulospora laevis root colonization and spore number in the root zone region. Mass production of A. laevis was observed in terms of percentage root colonization and spore population. The pot culture experiment was conducted in the polyhouse controlled conditions and observations were recorded at 30, 60, 90 and 120 days of plant growth. For percentage root colonization, lemon grass and vermicompost gave the best results (100Â±0), while the spore count was maximum with Sesbania aculeata and vermicompost. The data regarding the increase in VAM spore count and percentage root colonization were found statistically significant at different levels of probability in all the cases. Two way analysis revealed that the factor of time duration was more significant than the other factor of different substrates used on both spore count and root colonization.